2018
DOI: 10.1101/292607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peptidoglycan precursor synthesis along the sidewall of pole-growing mycobacteria

Abstract: 1 2 D-amino acid probes label cell wall peptidoglycan at both the poles and sidewall of pole-growing 3 mycobacteria. Since peptidoglycan assembly along the cell periphery could provide a rapid, 4 growth-independent means by which to edit the cell wall, we sought to clarify the precise 5 metabolic fates of these probes. D-amino acid monopeptides were incorporated into 6 peptidoglycan by L,D-transpeptidase remodeling enzymes to varying extents. Dipeptides were 7 incorporated into cytoplasmic precursors. While di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 74 publications
(138 reference statements)
3
31
0
1
Order By: Relevance
“…We hypothesized that the AGM synthesis that we observe under carbon deprivation ( Figure 1C ) is a cell-wide response, similar to peptidoglycan repair. Quantitative fluorescence microscopy revealed that O-AlkTMM labeling of M. smegmatis growing in carbon-replete medium comprised polar gradients ( Figure 1F ) as expected (Foley et al, 2016; Garcia-Heredia et al, 2018). However, in slow or non-growing, carbon-deprived M. smegmatis , O-AlkTMM-labeled species were more evenly distributed around the periphery of the cell.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…We hypothesized that the AGM synthesis that we observe under carbon deprivation ( Figure 1C ) is a cell-wide response, similar to peptidoglycan repair. Quantitative fluorescence microscopy revealed that O-AlkTMM labeling of M. smegmatis growing in carbon-replete medium comprised polar gradients ( Figure 1F ) as expected (Foley et al, 2016; Garcia-Heredia et al, 2018). However, in slow or non-growing, carbon-deprived M. smegmatis , O-AlkTMM-labeled species were more evenly distributed around the periphery of the cell.…”
Section: Resultssupporting
confidence: 58%
“…We previously showed that the fluorescent D-amino acid HADA and alkDala incorporate into M. smegmatis peptidoglycan via both cytoplasmic and L,D-transpeptidase enzymes (Garcia-Heredia et al, 2018). HADA and alkDala labeling roughly correlated with mycobacterial growth rate under different amounts of glucose or acetate ( Figures 1C, S1B, S1C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycobacteria must retain this complex cell envelope as they grow and extend their rod-shaped cell. New components for cell envelope extension are added at the subpolar regions (612). The intracellular membrane domain (IMD) is distinct from the conventional plasma membrane, and is found enriched in the subpolar regions of actively growing cells (13, 14).…”
Section: Introductionmentioning
confidence: 99%